Focused cardiac ultrasound is feasible in parturients; a prospective observational study. Issue 9 (22nd August 2017) - Jain, D.; Grejs, A. M.; Bhavsar, R.; Bang, U.; Sloth, E.; Juhl‐Olsen, P.
Abstract : Background: In pregnancy, the major causes of morbidity and mortality include diseases that affect circulation profoundly and restoration of normal circulation is a key objective. Focused cardiac ultrasound provides information on the individual determinants of circulation and has a significant impact on patient management. This study aimed to determine the feasibility of focused cardiac ultrasound in term parturients. Methods: Forty parturients underwent focused cardiac ultrasound. Parasternal long‐axis, parasternal short‐axis, 4‐chamber and subcostal views were performed in the left‐lateral position and the supine position by a novice operator. All images were graded on the following scale: 1 = no image; 2 = poor and insufficient image; 3 = sufficient image quality; 4 = good image quality; 5 = perfect image quality. A cut‐off grade of three signified images sufficient for clinical decision‐making. Results: Images sufficient for clinical decision‐making were obtained in all patients when including all imaging views. 37/40 (93 %) patients presented images of grade ≥ 4, whereas 10/40 (25%) patients had images of grade 5. Image grades were higher in the left lateral position (all P < 0.001). Parturients with a body mass index ≤ 30 kg/m 2 did not present different image grades than parturients with a higher body mass index ( P = 0.753). Subcostal views could not be obtained. Conclusion: Focused cardiac ultrasound is feasible in the obstetric population and images of sufficient quality for clinical decision‐making were obtained in all parturients by an operator with limited experience.